Fragment analysis in forensic anthropology - Douglas H. Ubelaker; Yaohan Wu (Oxford University Press, 2020)
Anthropological analysis of fragmentary evidence can be challenging but diverse methods allow substantial information to be gleaned. Scanning electron microscopy/energy dispersive X-ray spectroscopy enables determination if bone and/or tooth tissue is present. Protein radioimmunoassay or DNA analysis can establish the species present. Histological analysis can assist in species determination and reveal information about thermal changes. Radiocarbon analysis with special reference to the modern bomb-curve can clarify the postmortem interval. Anthropologists should also be aware that DNA analysis not only can enable positive identification but assist in the evaluation of sex and age at death.